VISUALISASI BUKU CERITA BERGAMBAR PUTRI TUJUH PROVINSI RIAU PELESTARIAN NILAI-NILAI TRADISIONAL - MELIANI OKTAVIA, Ir. Drs. Heldi, M.Si., Ph.D., Elia Pebriyeni, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The purpose of designing this Picture storybook of Putri tujuhis to preserve traditional values, so people could care more about theircultural heritage. The method of data analysing indesigning this Picturestorybook of Putri Tujuh is 5W 1H which data have been obtainedthrough observation, interview, survey and literature. The book isdesigned using related theories such as visual communication design,layout, illustration, and typography. Beside the main media, there arealso posters, digital posters, x-banners, mugs, totebag, t-shirts, notebooksand postcards which will be use as media support.Keywords: Folktale, Riau, Putri Tujuh